The innovation policy of the European Union : from government to governance - Borrás, Susana (Cheltenham, U.K. ; Northhampton, MA : Edward Elgar, 2003)
With a strong inter-disciplinary approach, this book analyses the politics and economics of the new innovation policy of the EU in chapters about research and knowledge production, the changing regime of intellectual property rights, building the information society and the world of standards.
Includes bibliographical references and index.
aia 19/8/16
Loans
Keywords: European Union; Technological innovations--Government policy; Information society--Government policy; Knowledge management--Government policy; Europe